REPRESENTATION AND NOVELTY IN AESCHYLUS' THEOROI. (29th December 2019) - THOMAS, OLIVER
Abstract: This article argues in favour of the view that in Theoroi (a.k.a. Isthmiastai ) the satyrs had absconded from Dionysus' choral training, and dedicate a set of votive masks on Poseidon's Isthmian temple. I propose that at the end of fr. 78c Dionysus offers them javelins and suggests that they dance a pyrrhikhe . This plot rests on a blurring of the distinctions between satyr, human character, and human performer. I interpret how Aeschylus managed plot, scenery, masks, costume, and language in order to transform this blurring to elicit from the audience humorous reflection on the nature of dramatic innovation and of drama as a representational medium.